Rispetta la montagna – Risparmia l’acqua e riduci i rifiuti quando visiti le Dolomiti WHS - Berger, Elisabeth; Bussadori, Virna; Morandini , Marcella (Restauro Archeologico, 2023)
In 2009, the Dolomites have been inscribed in the World Heritage List as a serial property for criteria VII and VIII. In recent years, the Dolomites have become an even much more attractive destination for visitors. Many of them do not know how to behave appropriately in this sensitive environment. The Covid19 pandemic has further accelerated these phenomena. With the project "Respect the mountain" (DE: Achtsam am Berg; IT Rispetta la montagna), an awareness-raising process is being implemented since 2021 in South Tyrol, addressing visitors, locals, and tourism professionals in the area of the Dolomites WHS. It aims to raise awareness of environmentally friendly behavior, with focus on water saving and waste reduction. The project is a cooperation between the Department of Nature, Landscape and Spatial Development of the Autonomous Province of Bolzano-South Tyrol - Coordination Office Dolomites UNESCO World Heritage, IDM South Tyrol and the Agency for Environment and Climate Protection of the Autonomous Province of Bolzano-South Tyrol. Tourism associations oversee the implementation.